Effects of Attenuated S. agalactiae Strain YM001 on Intestinal Microbiota of Tilapia Are Recoverable - Li, Ming; Li, Liping; Huang, Ting; Liu, Yu; Lei, Aiying; Ma, Chunxia; Chen, Fuyan; Chen, Ming (Frontiers in Microbiology, 2019)
Previously, we contructed and characterized the vaccine efficacy of attenuated S. agalactiae strain YM001 in tilapia. In this study, the potential impacts of YM001 on the tilapia intestinal flora were assessed by qPCR and 16S rRNA sequencing methods. The results showed that YM001 distributed unevenly in different parts of intestine, peaked in the intestine at 12 h after oral administration, and then declined gradually. YM001 caused 0% mortality of fish during the entire experimental period, while the referent strain HN016 caused 100% mortality at 3 d after oral administration. However, the intestinal flora could be changed by YM001, the diversity of intestinal flora decreased first and gradually recovered after oral administration. The diversity of intestinal flora of tilapia was negatively correlated with the content of HN016 in the intestinal tract. The oral YM001 mainly changed the abundance of Streptococcus, Cetobacterium, Akkermansia, Romboutsia, Bacteroides, Brevinema, Lachnospiraceae_NK4A136-group, coprothermobactter, presiomonas and Roseburia in intestine. The present study indicate that oral administration of YM001 altered the diversity and composition of intestinal flora in tilapia, but these change were only temporary, non-lethal, and recoverable. The results provide a more comprehensive experimental basis for the safety of oral YM001 vaccines.